IMPLEMENTASI PROGRAM KELUARGA SEHAT DALAM PEMBERDAYAAN ORANG TUA MENANAMKAN KEBIASAAN HIDUP BERSIH DAN AKTIF PADA ANAK DI DESA WINONG MANCAK, KABUPATEN SERANG - Mukhlis, Ahmad; Lesmana, Ihwan Satria; Fidziah, Fidziah; Triana, Leni; Sukmawan, Irwan; Komarudin, Mamay (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
This community service activity aimed to enhance parents’ role in instilling clean and active lifestyle habits in children in Desa Winong Mancak, Serang Regency. The methods included training, household mentoring, and group discussions conducted in March. Results indicated a significant improvement in parents’ knowledge and awareness of healthy lifestyles, implementation of cleanliness habits at home, and increased physical activity among children. Mentoring and group discussions strengthened parents’ motivation and commitment to maintain healthy habits. This program effectively empowers parents as change agents within families and communities. Recommendations for follow-up include forming parent working groups and continuous support from village authorities to sustain healthy habits with long-term positive impacts